2018
DOI: 10.1038/s41388-018-0534-3
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic microRNA-411 promotes lung carcinogenesis by directly targeting suppressor genes SPRY4 and TXNIP

Abstract: Lung cancer is one of the most common malignant diseases globally, composed of non-small cell lung cancer (NSCLC, 85%) and small cell lung cancer (SCLC, 15%). MicroRNAs (miRNAs) are single-stranded noncoding RNAs having important roles in lung cancer development. miR-411-5p/3p were reported to be increased significantly in human NSCLC tissues and cell lines. Moreover, miR-411-5p/3p overexpression could accelerate cell proliferation and migration, and impede cell apoptosis in NSCLC cell lines. Mechanically, SPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…Oncogenic activation of PI3K/AKT signaling at least partially promotes cellular glucose uptake through the regulation of TXNIP expression [45]. Previous cancer studies have reported that TXNIP is regulated by miR-373 [46], miR-411 [47], and miR-224 [48,49]. Our study is the first to show TXNIP as an miR-20b target in GC.…”
Section: Discussionsupporting
confidence: 58%
“…Oncogenic activation of PI3K/AKT signaling at least partially promotes cellular glucose uptake through the regulation of TXNIP expression [45]. Previous cancer studies have reported that TXNIP is regulated by miR-373 [46], miR-411 [47], and miR-224 [48,49]. Our study is the first to show TXNIP as an miR-20b target in GC.…”
Section: Discussionsupporting
confidence: 58%
“…For example, miR‐155‐5p can inhibit the proliferation, migration, and invasion of NSCLC cells via regulating high‐mobility group box . While miR‐411 can promote lung carcinogenesis by directly targeting suppressor genes SPRY4 and TXNIP . Furthermore, serum levels of miRNAs might be diagnostic markers differ among the stages of NSCLC patients .…”
Section: Introductionmentioning
confidence: 99%
“…D-allose can increase TXNIP expression at both protein and mRNA levels, thereby inhibiting the growth of NSCLC (115). The micro RNA miR-411-5p/3p is significantly upregulated in human NSCLC tissues and cell lines, and the overexpression of miR-411-5p/3p can inhibit the expression of SPRY4 and TXNIP, which in turn promote tumor proliferation and migration, preventing apoptosis in NSCLC cell lines (102).…”
Section: Cancers Of the Respiratory System And Others (Table 3) Txnipmentioning
confidence: 99%